OVERVIEW SELF EFFICACY OF SPIRITUAL AND PATIENTS HIV/AIDS IN THE PROVINCE BENGKULU - Ismatul Zahara; Sardaniah Sardaniah; Tuti Anggriani Utama (Universitas Bengkulu, 2021)
Our objective is to see the picture of self-efficacy, and the level of spirituality of HIV / AIDS patients in Bengkulu Province. The results of this study can be used to increase the client's knowledge about the importance of self-efficacy, and spiritual level of the HIV / AIDS patient itself. Its Benefits As an ingredient consideration for further research as well as motivating researchers to read the latest issues and trends regarding HIV / AIDS, especially in the Province Bengkulu. using this type of descriptive research in order to explain how to describe self-efficacy and spiritual level in HIV / AIDS patients at Bengkulu Province. (Nursalam 2008, in Henni, 2011) The population in this study are all HIV / AIDS positive clients, amounting to 177 people in the Province Bengkulu.used was Thepurposive sampling sample123 people were sampled with certain criteria (Hardani, 2020). The results show most PLHIV in Bengkulu Province in this study have self efficacy sufficientthat about 24 out of 50 respondents enter into it category of ODHA with Self Efficacy sufficient. and on spiritual variables some ODHA respondents in Bengkulu Province have a high spiritual level where this is supported by the results of the study that of the 50 respondents 41 people fall into the category of a high spiritual level. The benefits of research can be additional literature for nursing institutions regarding aspects of self-efficacy and spiritual in order to create a characteristic nurse. ODHA is expected to increase knowledge about Self Efficacy and Spiritual level in order to be able optimize existing support and guidance resources. Researchers hope there is further research related to other factors that affect health especially for people living with HIV / AIDS. .